Eksistensi Tuhan Dalam Tasawuf Emha Ainun Nadjib - Faiz Fauzi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2018)
One of the poets, writers, artists, writers, cultural artists who popularized the popular mass media in the 1980s to the 1990s, is Emha Ainun Nadjib or Emha. His works found many religious and spiritual discourses, especially in his essays and poems. This study highlights Emha’s thoughts about the Existence of God within the framework of Sufism. The results of the study explained that the process of natural creation lasted for six days. The cycle will eventually be reunited with God. God’s execution according to Emha is the Emanation of God within the framework of the wahdah al-wujud. All come from God and will reunite with God (al-Haq).[Salah satu penyair, penulis, seniman, sastrawan, budayawan yang mewarnasi media massa yang popular diera 1980 hingga 1990-an yaitu Emha Ainun Nadjib atau Emha. Karya-karyanya banyak ditemukan wacana religious dan spiritual, khususnya dalam esai dan puisinya. Kajian ini menyoroti tentang pemikiran Emha tentang Eksistensi Tuhan dalam kerangka tasawuf. Hasil dari kajian menjelaskan bahwa proses penciptaan alam berlangsung selama enam hari. Siklus tersebut pada akhirnya akan manunggal (menyatu) kembali bersama Allah. Eksestensi Tuhan menurut Emha adalah Emanasi Tuhan yang dalam kerangka wahdah al-wujud. Semua berasal dari Allah dan akan menyatu kembali dengan Allah (al-Haq).]